Instruments for Development Controls in Gerbangkertosusila - Pamungkas, Adjie; Rini, Erma Fitria; Cahyo, Prio Nur (The ITB Journal Publisher, 2016)
Gerbangkertosusila (GKS) is one of the national strategic areas (KSN) consisting of 7 municipal and 1 provincial governments. The main objective of KSN is to accelerate and coordinate the development process on the macro level including arterial and toll road systems, development around the Suramadu Bridge Area, and regional seaport development. However, the development acceleration and coordination among the municipalities is still inadequate. Therefore, a partnership among parties is needed to promote and control development within GKS. Consequently, agreed instruments of development control are some of the key steps for successful partnerships.To agree on development control instruments, stakeholders are required to assess 60 proposed instruments within the four groups of development control (zoning, planning permits, sanction and development incentives and disincentives). Based on the questionnaire outputs, stakeholders consider the roles of municipal authority far greater than the provincial level and the body of GKS. The body of GKS is suggested to serve only in coordination the three main development activities (planning, implementation and controlling). The output of the questionnaire was then re-assessed and agreed by stakeholders in a focus group discussion (FGD). In the FGD, stakeholders agreed that the municipal and provincial governments have similar roles in implementation and monev (monitoring and evaluating) of developments. The body of GKS is directed to coordinate, monitor and evaluate key development projects in GKS. The FGD also resulted in agreed instruments, which are; 2 instruments in zoning, 4 instruments in permits, 10 instruments in sanction, 17 instruments in development incentives and 5 instruments in development disincentives. The role of coordination and monev of the GKS body is also highlighted via development schemes in every agreed instrument.Keywords. Instruments, development control, GKS, coordination.Â Gerbangkertosusila (GKS) adalah salah satu kawasan strategis nasional (KSN) yang terdiri dari 7 kota/ kabupaten dan 1 propinsi. Tujuan utama KSN adalah untuk mempercepat dan mengkoordinasikan proses pembangunan pada tingkat makro termasuk sistem jalan arteri dan tol, pembangunan di sekitar Kawasan Jembatan Suramadu, dan pembangunan pelabuhan wilayah. Namun, percepatan dan koordinasi pembangunan diantara pemerintah daerah masih belum memadai. Oleh sebab itu, kerja sama diperlukan untuk mempromosikan dan mengendalikan pembangunan di GKS. Sebagai konsekuensinya, instrumen pengendalian pembangunan yang disetujui merupakan langkah kunci untuk keberhasilan kerja sama tersebut.Berdasarkan hasil analisis kuesioner, pemangku kepentingan menganggap bahwa peran pemerintah kota/ kabupaten jauh lebih penting daripada provinsi dan lembaga wilayah. Dalam FGD, para pemangku kepentingan sepakat bahwa lembaga wilayah diarahkan untuk mengkoordinasikan, memonitor dan mengevaluasi proyek-proyek pembangunan kunci GKS. FGD juga menyetujui perlunya sejumlah instrumen berupa zoning, perijinan, sanksi, insentif dan disinsentif.Kata Kunci: instrumen, pengendalian pembangunan, GKS, koordinasi.